2004
DOI: 10.1007/s00221-003-1690-3
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal brain-based feedback and communication system

Abstract: The Thought Translation Device (TTD) is a brain-computer interface based on the self-regulation of slow cortical potentials (SCPs) and enables completely paralyzed patients to communicate using their brain potentials. Here, an extended version of the TTD is presented that has an auditory and a combined visual and auditory feedback modality added to the standard visual feedback. This feature is necessary for locked-in patients who are no longer able to focus their gaze. In order to test performance of physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 16 publications
2
98
1
Order By: Relevance
“…Despite the visual system being the sensory input that produces the best improvements in learning processes [8] there are many situations where other types of feedback are required, due to the pathology itself or requirements of the rehabilitation process. This is the reason supporting the first attempts to analyze from a psychological point of view different feedback modalities in complex settings, such as driving a wheelchair [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the visual system being the sensory input that produces the best improvements in learning processes [8] there are many situations where other types of feedback are required, due to the pathology itself or requirements of the rehabilitation process. This is the reason supporting the first attempts to analyze from a psychological point of view different feedback modalities in complex settings, such as driving a wheelchair [3].…”
Section: Introductionmentioning
confidence: 99%
“…Steady-state visual evoked potentials have been used for binary selection, [48][49][50][51] both discrete and continuous control of a cursor in 2 dimensions, 52 prosthesis control, 53 FES, 54,55 spelling, 56 and environmental control. 57 For patients with impaired vision, various auditory 39,40,[58][59][60][61] and tactile [62][63][64][65] paradigms have been investigated. A few studies are now focused on the critical need to move BCI systems out of the laboratory and into patients' homes, which raises many complex patient, caregiver, and implementation issues.…”
Section: Device Outputmentioning
confidence: 99%
“…for instance, self modulation by imagination of movements can result in changes in EEG rhythm in central region of the scalp overlying the sensorimotor cortex [3] [8] [33] [45]. These rhythms are the basis of several BCI systems [3] [8] in which imagination of hand movement gives rise to an amplitude suppression in the α-band (8-12 Hz) and β-band (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 4 rhythms over the contralateral primary hand motor cortical area [33]. Wolpaw and co-workers [43] [45] used continuous changes in the amplitudes of these rhythms to move a cursor in a computer screen.…”
Section: Bci Research and Ibci Systemmentioning
confidence: 99%
“…Attentional modulation seems to constitute the cognitive strategy in the physiological regulation of SCP. The team lead by Birbaumer has widely shown that healthy subjects as well as severely paralyzed patients can learn to self-control their SCPs through operant conditioning to move an object on a computer screen in a BCI referred to as Thought Translation Device (TTD) [17].…”
Section: Bci Research and Ibci Systemmentioning
confidence: 99%